Durability of Concrete on Base Building Waste - Jasur, Tursunov; Sultonbek, Babayev (European Journal of Life Safety and Stability (2660-9630), 2023)
In this work, the authors discuss the feasibility of using some construction debris to generate high-performance concrete (HPC). Recycled Concrete Aggregate (RCA) of 5-20 mm fraction was used to make the mixtures. Concretes containing RCA were combined with 300 kg/m3 of various cements. The sample specimens of concrete were evaluated for their mechanical qualities and some properties relevant to durability. After 28 days, the compressive strength reaches 55.5 MPa, and after 90 days, it reaches 60.4 MPa.